USP18 enhances the resistance of BRAF-mutated melanoma cells to vemurafenib by stabilizing cGAS expression to induce cell autophagy - Ma, Zhou-rui; Xiong, Qian-wei; Cai, Shi-zhong; Ding, Ling-tao; Yin, Chao-hong; Xia, Hong-liang; Liu, Wei; Dai, Shu; Zhang, Yue; Zhu, Zhen-hong; Huang, Zhi-jian; Wang, Qian; et al. (International immunopharmacology, 2023)
•cGAS was increased in vemurafenib-resistant patients with BRAF V600E mutant melanoma.•Knockdown of cGAS inhibited the resistance to vemurafenib in A2058R cells.•USP18 could deubiquitinate cGAS to promote its protein stability.•USP18 promoted vemurafenib-induced protective autophagy by stabilizing cGAS protein.•Our study highlighted the significance of USP18 in BRAF V600E mutant melanoma. This study aims to discern the possible molecular mechanism of the effect of ubiquitin-specific peptidase 18 (USP18) on the resistance to BRAF inhibitor vemurafenib in BRAF V600E mutant melanoma by regulating cyclic GMP-AMP synthase (cGAS). The cancer tissues of BRAF V600E mutant melanoma patients before and after vemurafenib treatment were collected, in which the protein expression of USP18 and cGAS was determined. A BRAF V600E mutant human melanoma cell line (A2058R) resistant to vemurafenib was constructed with its viability, apoptosis, and autophagy detected following overexpression and depletion assays of USP18 and cGAS. Xenografted tumors were transplanted into nude mice for in vivo validation. Bioinformatics analysis showed that the expression of cGAS was positively correlated with USP18 in melanoma, and USP18 was highly expressed in melanoma. The expression of cGAS and USP18 was up-regulated in cancer tissues of vemurafenib-resistant patients with BRAF V600E mutant melanoma. Knockdown of cGAS inhibited the resistance to vemurafenib in A2058R cells and the protective autophagy induced by vemurafenib in vitro. USP18 could deubiquitinate cGAS to promote its protein stability. In vivo experimentations confirmed that USP18 promoted vemurafenib-induced protective autophagy by stabilizing cGAS protein, which promoted resistance to vemurafenib in BRAF V600E mutant melanoma cells. Collectively, USP18 stabilizes cGAS protein expression through deubiquitination and induces autophagy of melanoma cells, thereby promoting the resistance to vemurafenib in BRAF V600E mutant melanoma.